Towards an International Code of Conduct for Private Security Providers: A View from Inside a Multistakeholder Process - Buzatu, Anne-Marie (SSR Papers, 2015)
The use of private security companies (PSCs) to perform services that are traditionally associated with the state presents a challenge to regulatory and oversight frameworks. Analyzing developments leading to the International Code of Conduct for Security Providers (ICOC) and the ICOC Association, this paper argues that a multistakeholder approach to develop standards adapted for the private sector and which creates governance and oversight mechanisms fills some of the governance gaps found in traditional regulatory approaches.